НЕАЛКОГОЛЬНАЯ ЖИРОВАЯ БОЛЕЗНЬ ПЕЧЕНИ: ОТ ТЕОРИИ К ПРАКТИКЕ - П. В. Селивёрстов (SINAPS LLC, 2015)
Non alcoholic hepar diseases (NAHD) is actual problem in the world medical servises. Despite to many new methods of diagnosis ant new pharmaceutical remedies, there are a lot of questions in many aspects of pathogenesis, diagnosis, treatment and prophilaxis of this diseases. First of all, NAHD is nosological form of disease, and from the other hand, in fact NAHD is real risk factor occur in cardiovascular diseases. Main optimal goal in this situation in therapy NAHD must be prophilaxis in hepar pathology and decreasing the level of risk cardiovascular complications. According to this general position it is actual issues to find optimal parametres in treatment with new pharmaceutical remedies for NAHD, what was our main goal in this publication with discussions.